Solitons at the zero dispersion wavelength of single-mode fibers - Menyuk, Curtis; Wai, Ping-Kong A.; Chen, H. H.; Lee, Y. C. (Optica, 1986)
In modern day low-toss single-mode fiber, the maximum information transmission rate is determined by chromatic dispersion. At most carrier wavelengths, the pulse broadening dispersion effect can be adequately described by the second- order dispersion coefficient β″ = ∂²β/∂ω², where β is the propagation constant. One way to avoid spreading of the pulse transmitted by the fiber is to operate at the so-called zero dispersion wavelength, at which the second-order dispersion vanishes, β″ = 0. For silica fiber, this wavelength is 1.27 μm. it can be shifted to 1.55 μm to take advantage of the minimum, fiber loss of 0.2 dB/km in specially designed fiber. However, even at this wavelength, it has been shown¹ that higher-order dispersion can cause significant pulse broadening. Another method to counter the dispersion, proposed by Hasegawa and Tappert,² is to make use of the nonlinearity of the refractive index, the Kerr effect, to balance the second-order dispersion. Soliton pulses (or more precisely solitary waves) could then be generated which propagate without dispersive broadening. Recent experiments³,⁴ have shown the feasibility of this idea by demonstrating the propagation of solitons in the anomalous dispersion region of a single-mode silica fiber. However, whether such balance would occur between the nonlinearity and the higher-order dispersion at the zero dispersion wavelength is unclear.
International Quantum Electronics Conference 1986, San Francisco, California United States, 9–13 June 1986
Keywords: Fiber losses; UMBC Optical Fiber Communications Laboratory; Dispersion; Single mode fibers; Silica fibers; Refractive index; Kerr effect